Phototransformation of pollutants using lutetium and zinc phthalocyanines anchored on electrospun polymer fibers - Zugle, Ruphino (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
Novel lanthanide phthalocyanines containing dysprosium, erbium and lutetium as central metals were synthesized using phthalonitrile:metal salt ratio of 4:1 or lower phthalonitrile content as well as using unmetallated phthalocyanine. They were characterized using various spectroscopic and elemental analyses. Dysprosium bis-phthalocyanine was obtained while monomers were obtained for erbium and lutetium phthalocyanines. Theopen-shelldysprosiumbis-phthalocyanine and the monomeric complex of the open-shell erbium were neither fluorescent nor showed the ability to generate singlet oxygen. The triplet states of all the lutetium phthalocyanines were found to be populated with high triplet quantum yields and corresponding high singlet oxygen quantum yields. The fluorescence quantum yields of the lutetium phthalocyanines were however found to be very low. The lutetium phthalocyanines together with unsubstituted zinc phthalocyanine and its derivatives were successfully incorporated into electrospun polymer fibers either by covalent linkage or sorption forces. Spectral characteristics of the functionalized electrospun polymer fibers indicated that the phthalocyanines were bound and their integrity maintained within the fiber matrices. Most importantly the fluorescence and photoactivity of the phthalocyanines were equally maintained within the electrospun fibers. The functionalized electrospun polymer fibers especially those containing the zinc phthalocyanines could qualitatively detect nitrogen dioxide, a known environmental air pollutant. Also all the functionalized electrospun polystyrene and polysulfone fibers containing lutetium and zinc phthalocyanines could be applied for the photoconversion of 4-chlorophenol, 4-nitrophenol and methyl orange. Those of polystyrene could be re-used. Polyacrylic acid and polyurethane functionalized electrospun fibers were found not to be suitable for photocatalytic applications in aqueous medium. 4-Chlorophenol was found to be more susceptible to photodegradation while methyl orange very difficult to degrade.
Keywords: Electrospinning; Phthalocyanines; Lutetium; Zinc; Polymers; Dysprosium; Pollutants; Air -- Pollution; Photochemistry